2021
DOI: 10.1002/celc.202101161
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electrochemical Cell Microscopy in a Glovebox: Structure‐Activity Correlations in the Early Stages of Solid‐Electrolyte Interphase Formation on Graphite

Abstract: Understanding the formation and properties of the solidelectrolyte interphase (SEI) will enable the development of enhanced Li-ion batteries (LiBs) and other battery types. Herein, we report scanning electrochemical cell microscopy (SECCM) in a glovebox to characterize the SEI formation on the basal surface of highly oriented pyrolytic graphite (HOPG) as a model system of negative LiB electrodes with nonaqueous electrolytes. Different grades of HOPG have been studied, which provide a range of step edge densiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 81 publications
0
44
0
2
Order By: Relevance
“…SECCM has been used to study positive electrode materials such as single LiMn 2 O 4 , [31] and LiFePO 4 [32] particles in aqueous electrolytes, but has only recently been implemented in a glovebox to study materials for Li-ion cells under inert atmosphere, [33,34] such as SEI formation on graphite. [34] In this work, we report a powerful combinatorial screening method to characterise battery materials and its application to study SEI formation and properties on Si negative electrodes for Li-ion cells. This combinatorial method is made possible by the high-throughput spatiallyresolved nature of SECCM and correlative chemical analysis of the SEI composition by SHINERS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SECCM has been used to study positive electrode materials such as single LiMn 2 O 4 , [31] and LiFePO 4 [32] particles in aqueous electrolytes, but has only recently been implemented in a glovebox to study materials for Li-ion cells under inert atmosphere, [33,34] such as SEI formation on graphite. [34] In this work, we report a powerful combinatorial screening method to characterise battery materials and its application to study SEI formation and properties on Si negative electrodes for Li-ion cells. This combinatorial method is made possible by the high-throughput spatiallyresolved nature of SECCM and correlative chemical analysis of the SEI composition by SHINERS.…”
mentioning
confidence: 99%
“…In this regard, scanning electrochemical cell microscopy (SECCM) [28,29] is a high-throughput technique [30] with high spatial resolution that allows thousands of individual electrochemical measurements to be made with control of experimental conditions. SECCM has been used to study positive electrode materials such as single LiMn 2 O 4 , [31] and LiFePO 4 [32] particles in aqueous electrolytes, but has only recently been implemented in a glovebox to study materials for Li-ion cells under inert atmosphere, [33,34] such as SEI formation on graphite. [34] In this work, we report a powerful combinatorial screening method to characterise battery materials and its application to study SEI formation and properties on Si negative electrodes for Li-ion cells.…”
mentioning
confidence: 99%
“…234 Environmental control during the experiment has been another major point of interest. 209,226,[235][236][237][238][239] Oil has been used to cover the substrate and restrict gas exchange from the meniscus; 226 while small containers connected to a gas supply were utilized to establish specific atmospheric conditions. Recently, SECCM measurements have been conducted inside a glovebox, 236,239,240 and aided by a thorough understanding of the behavior of non-aqueous electrolyte media, 241 they have set the groundwork for future work into battery materials.…”
Section: Technical and Theoretical Developmentsmentioning
confidence: 99%
“…Slow scan rate SECCM voltammetry revealed that step edges promote electrolyte reduction resulting in a more passivating SEI layer than on the basal plane. 236 In recent work, SECCM measurements were coupled with enhanced Raman spectroscopy monitoring via shell-isolated nanoparticles (SHINERS technique, Figure 11D). 240 Two different aprotic electrolyte systems (ethylene carbonate/ethyl methyl carbonate, vol.…”
Section: Battery Electrode Materialsmentioning
confidence: 99%
“…The development of local electrochemical techniques such as scanning electrochemical microscopy (SECM) [1,2], scanning vibrating electrode technique (SVET) [3], and scanning microcell [4] or scanning electrochemical cell microscopy (SECCM) [5], has enabled local reactivity measurements of various types of interfaces at different length scales. These techniques have been utilized to measure surface heterogeneity of interfaces including the solid electrolyte interphase formation on graphite [6], electrocatalytic materials [7], corroding metals [8], and bio-surfaces and interfaces [9].…”
Section: Introductionmentioning
confidence: 99%